Manufacturing process of lightweight positive plate grid
Through stamping molding and surface treatment technology of lead-calcium rare earth alloy, the problems of poor bonding and brittle cracking of the positive electrode grid of lead-acid battery are solved, and high-efficiency and lightweight production is achieved, reducing production costs and return rates, and meeting the new The lightweight requirement of national standards.
Patent Information
- Application Number
- CN202411279876.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-27
AI Technical Summary
The existing lead-acid battery positive grid stamping technology has problems such as poor binding force and high brittle cracking scrapping rate, making it difficult to achieve lightweight and efficient production, and the traditional casting method has problems such as high cost and large equipment investment.
Lead-calcium rare earth alloy is used as the positive electrode grid material, and aging hardening and surface treatment is carried out after stamping and forming, including methanesulfonic acid tank immersion, pure sink cleaning, lead-antimony alloy electrodeposition and baking to form a stable surface hierarchy structure. Improve the binding force of active substances and grids.
The high-efficiency stamping of the positive electrode grid is achieved, which reduces water loss and early capacity loss problems, improves the binding force between the grid and active substances, reduces production costs, and increases the surface treatment process with limited costs, which improves the battery. Service life and productivity.
Smart Images

Figure CN119208622A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lead-acid batteries, and in particular to a manufacturing process of a lightweight positive electrode grid. Background Art
[0002] The release of the new national standard GB17761-2018 "Electric Bicycle Safety Technical Specifications" has put forward higher requirements for electric bicycles. The mass of a fully assembled electric bicycle is less than or equal to 55kg, and the nominal voltage of the battery is less than or equal to 48V. Therefore, the requirements for lead-acid batteries for electric bicycles are more stringent. The number of 12V batteries in the whole vehicle is limited to 4, and the weight must be lighter. Consumers' requirements for battery life or capacity will only be higher, which poses a huge challenge to the improvement of battery technology. About 70% of the weight of a lead-acid battery is due to the amount of lead used, and the reduction in the amount of active material is limited, so the lightweight technology of the grid has become a top priority.
[0003] Traditional lead-acid battery grids are formed by gravity casting of molds, while stamped grids are made of lead strips through repeated rolling, and then punched into the required grids through molds. The grids are light and low in cost. Grid stamping technology has the advantages of low energy consumption, large-scale production, high consistency, and high production efficiency. The negative electrode grid alloy is simple and stamping technology is easy to implement, but there are many problems in stamping the positive electrode grid.
[0004] The positive grid alloy of lead-acid batteries for electric bicycles is firstly lead-calcium alloy, but the positive grid of lead-calcium alloy adopts stamping technology. After repeated rolling and punching, the surface is too smooth, which is not conducive to forming a good bonding force with the active material, and the probability of a high resistance layer increases. The second is to use high antimony alloy. The grid has good lead paste bonding, but high antimony alloy is easy to gasify at the negative electrode when used in power batteries for electric bicycles. The battery loses water seriously due to excessive gas production, and even causes thermal runaway in severe cases. The third is to use low antimony alloy. Regarding the achievements of low-antimony grids, CN201710459061.8 discloses the invention patent "A lead-antimony rare earth alloy for power batteries". The alloy content is 1.2-1.8% antimony, 0.02-0.08% selenium, 0.3-0.8% tin, 0.02-0.05% silver, 0.008-0.02% lanthanum, 0.005-0.01% yttrium, 0.01-0.04% bismuth, and the rest is lead. The lead-antimony rare earth alloy of this invention has good fluidity, strong corrosion resistance, good creep resistance, and antimony is not easy to lose. The grid produced by casting has no defects such as pores and brittle cracks, which can solve the problems of poor bonding and excessive gas evolution. However, brittle cracks are prone to occur during stamping of the positive electrode grid, and the scrap rate is significantly increased, which greatly increases the manufacturing cost and reduces production efficiency.
[0005] Due to the above reasons, the industrial development of lightweight grids has brought great difficulties. Many companies still conservatively use the casting method to produce positive grids, and some companies boldly try various grid surface treatment methods. CN201610590038.8 discloses "A lead-acid battery grid surface treatment method", including cleaning the grid, using a glow discharge device to perform plasma discharge treatment on the surface of the cleaned grid, and other steps. By using plasma discharge treatment to form a nitrogen oxide film on the surface of the grid, without changing the existing production process, the bonding force between the electrode active materials such as lead paste and the grid is effectively improved, and the bonding force between the grid and the lead paste can be improved. However, this method requires investment in plasma discharge equipment, compressed air, ultrasonic equipment, etc., and cannot guarantee that the surface structure of the grid is completely undamaged, and there is a certain risk. Further, CN202311701698.5 discloses "A lead-acid battery grid corrosive agent formula and its preparation method", the formula includes pure water, sodium silicate, glacial acetic acid, hydrogen peroxide, baking soda, ammonium carbonate, the formula liquid is applied to the grid surface before applying the paste, and the surface lead (lead alloy) is kept closed and stationary at room temperature without light to accelerate the corrosion of the surface, which can accelerate the corrosion of the grid surface to form basic lead carbonate, the crystal layer thickness is uniform, grows on the grid surface, and fits tightly with the grid lead (lead alloy), so that the corrosion layer generated is in good contact with the grid alloy, the stratification is not obvious, the current density distribution is uniform during charging and discharging, the lead paste has good bonding with the grid, and the battery life is improved. All additives and products in the formula will volatilize, decompose or have no negative impact on battery performance in subsequent battery manufacturing, but the implementation effect may not be as obvious as expected.
[0006] How to achieve lightweighting of the positive electrode grid, adopt advanced grid stamping technology to replace the traditional casting process, and solve the problem of interface bonding strength between the grid and the active material caused by casting to stamping, as well as the high scrap rate of brittle cracking of stamping forming of low antimony alloys, are huge challenges facing the technical field of lead-acid batteries for electric bicycles. Summary of the invention
[0007] The present invention aims to provide a manufacturing process for a lightweight lead-acid battery positive grid, which can overcome the deficiencies of the prior art, achieve lightweighting of the positive grid, and at the same time improve the bonding strength between the grid and the active material, reduce production costs, and improve production efficiency.
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A manufacturing process for a lightweight positive electrode grid comprises the following steps:
[0010] S1. Using lead-calcium rare earth alloy as the positive electrode grid material, a preliminary grid is obtained by stamping;
[0011] S2. Performing aging hardening treatment on the stamped grid;
[0012] S3. Surface treatment is performed on the grid after age hardening. The specific steps include:
[0013] The grid is moved at a constant speed of 1 m / min through a 1 m long methanesulfonic acid tank for immersion;
[0014] The washed grid is sequentially passed through three 1m long pure water tanks for spray cleaning, and then dried by absorbent cotton.
[0015] The cleaned grid surface is subjected to lead-antimony alloy electrodeposition treatment, and the specific steps include: passing the grid through a 3m long conductive tank for electrodeposition, and then passing through four 1m long pure water tanks for upper and lower spray cleaning, and then passing through absorbent cotton to absorb water and dry again;
[0016] S4. The grid after the electrodeposition treatment is passed through a 1m long baking furnace for high temperature drying and then rolled into a roll.
[0017] As a further solution of the present invention: the lead antimony electrodeposition formula comprises: 171 g / L potassium antimony tartrate, 165 g / L tartaric acid, 100 mL / L benzenesulfonic acid, and 68.63 g / L basic lead carbonate.
[0018] As a further solution of the present invention: the concentration of methanesulfonic acid in the methanesulfonic acid tank is 70%, and the pickling time is 1 min to 2 min.
[0019] As a further solution of the present invention: in the electrodeposition process, the electrodeposition current density is 0.30A / dm 2 ~2.0A / dm 2 , the electrodeposition time is 1 to 3 minutes.
[0020] As a further solution of the present invention: the anode plate is a Pb-Sb alloy lead strip, and the distance between the cathode and the anode is 10 mm to 15 mm.
[0021] As a further solution of the present invention: the baking and drying temperature of the baking oven is set to 110±10° C., and the baking and drying time is 1 min to 3 min.
[0022] As a further solution of the present invention: before the electrodeposition treatment, the grid can also be subjected to an additional pretreatment step, such as soaking in a sugar alkali solution or electrolysis in a sodium carbonate electrolyte, to enhance the roughness of the grid surface and improve the electrodeposition effect.
[0023] Beneficial effects of the present invention: The grid treatment process can achieve high-efficiency stamping of the positive grid without the problem of excessive water loss of high-antimony alloy grid batteries, and solve the problem of early capacity loss without antimony effect. The surface treatment process added in the process is simple to implement, and the increase in cost is very limited, mainly due to the increase in the amount of water used for multi-stage rinsing, which is negligible compared with the economic benefits brought by responding to the new national standard lightweighting. Enterprises can sell more electric bicycles and achieve a lower return rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention will be further described below in conjunction with the accompanying drawings.
[0025] Figure 1 It is a schematic diagram of the process flow of the present invention;
[0026] Figure 2 is the SEM of the grid surface after soaking in sugar and alkali in Example 3;
[0027] Figure 3 The grid surface of Example 4 after bidirectional electrolysis of the cathode and anode forms a corrosion layer, and the grid surface SEM at this time;
[0028] Figure 4 This is the surface SEM of the electrodeposited coating of Example 5;
[0029] Figure 5 The SEM and EDS data of the coatings compared between Example 6 and Example 2;
[0030] Figure 6 This is the SEM of the grid surface before pickling;
[0031] Figure 7 This is the SEM of the grid surface after pickling;
[0032] Figure 8 This is the SEM of the grid surface before electrodeposition;
[0033] Fig. 9 This is the SEM of the grid surface after electrodeposition;
[0034] Fig.10 and Fig.11 It is the 100% DOD cycle curve of the acid-washed electrodeposition positive grid battery;
[0035] Fig.12 Single cell impedance diagram of the battery in Examples 1 and 2. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] See also Figure 1-12 As shown, the present invention is a manufacturing process of a lightweight positive electrode grid, comprising the following steps:
[0038] S1. Using lead-calcium rare earth alloy as the positive electrode grid material, a preliminary grid is obtained by stamping;
[0039] S2. Performing aging hardening treatment on the stamped grid;
[0040] S3. Surface treatment is performed on the grid after age hardening. The specific steps include:
[0041] The grid is moved at a constant speed of 1 m / min through a 1 m long methanesulfonic acid tank for immersion;
[0042] The washed grid is sequentially passed through three 1m long pure water tanks for spray cleaning, and then dried by absorbent cotton.
[0043] The cleaned grid surface is subjected to lead-antimony alloy electrodeposition treatment, and the specific steps include: passing the grid through a 3m long conductive tank for electrodeposition, and then passing through four 1m long pure water tanks for upper and lower spray cleaning, and then passing through absorbent cotton to absorb water and dry again;
[0044] S4. The grid after the electrodeposition treatment is passed through a 1m long baking furnace for high temperature drying and then rolled into a roll.
[0045] The lead antimony electrodeposition formula comprises: 171 g / L potassium antimony tartrate, 165 g / L tartaric acid, 100 mL / L benzenesulfonic acid, and 68.63 g / L basic lead carbonate.
[0046] The methanesulfonic acid concentration in the methanesulfonic acid tank is 70%, and the pickling time is 1 min to 2 min.
[0047] In the electrodeposition process, the electrodeposition current density is 0.30A / dm 2 ~2.0A / dm 2 , the electrodeposition time is 1 to 3 minutes.
[0048] The anode plate is a Pb-Sb alloy lead strip, and the distance between the cathode and the anode is 10mm to 15mm.
[0049] The baking and drying temperature of the baking oven is set to 110±10° C., and the baking and drying time is 1 min to 3 min.
[0050] Before the electrodeposition treatment, the grid may be subjected to an additional pretreatment step, such as soaking in a sugar-alkali solution or electrolysis in a sodium carbonate electrolyte, to enhance the roughness of the grid surface and improve the electrodeposition effect.
[0051] Embodiment 1:
[0052] Normal lead-calcium rare earth alloy is used to stamp the positive grid 22Y1, which is directly coated after aging hardening.
[0053] Example 1 6-DZF-20 battery assembled with grids was subjected to C2 cycle test. It was found that the impedance of some battery packs dropped significantly after 200 cycles. The impedance of a single cell was about 6.8mΩ, which is relatively high. Fig.12 .
[0054] Embodiment 2:
[0055] Normal lead-calcium rare earth alloy is used to stamp the positive electrode grid 22Y2. After aging hardening, the grid surface is treated.
[0056] In the first step, the 22Y2 grid roll is unwound and moved forward at a uniform speed of 1m / min. It is washed in a 1m long 70% methanesulfonic acid tank and then immediately passes through three 1m long pure water tanks with upper and lower water inlets to spray and clean the grid surface. After cleaning, the cleaned grid is dried by water absorption cotton.
[0057] Preferably, the pickling time is 1 min to 2 min;
[0058] Preferably, the pure water tank is configured for three-stage water washing, and each water inlet is connected to a water storage tank, which is flowing circulating water and can be recycled.
[0059] In the second step, the surface of the pickled grid is subjected to lead-antimony alloy electrodeposition treatment. The specific steps include: the grid passes through a 3m long conductive tank in turn, and the clarified electrodeposition plating solution is placed in the tank. After 3 minutes of electrodeposition, a Pb-Sb alloy coating is formed on the surface of the grid. After that, the grid passes through four 1m long pure water tanks in turn, and is sprayed up and down to be cleaned. After the plating solution is cleaned, the grid is dried by water-absorbing cotton;
[0060] Preferably, the lead antimony electrodeposition formula adopts: 171g / L potassium antimony tartrate, 165g / L tartaric acid, 100mL / L benzenesulfonic acid, and 68.63g / L basic lead carbonate.
[0061] Preferably, the electrodeposition plating tank is left to stand without stirring;
[0062] Preferably, the anode plate is a Pb-Sb alloy lead strip with a thickness of about 2 mm;
[0063] Preferably, the distance between the cathode and the anode is 10 mm to 15 mm;
[0064] Preferably, the electrodeposition current density is 0.30A / dm2 to 0.60A / dm2, and the electrodeposition time is 3min;
[0065] Preferably, the pure water tank is configured for four-stage water washing, and each water inlet is connected to a water storage tank, which is flowing circulating water and can be recycled.
[0066] In the third step, the grid after electrodeposition treatment is dried at high temperature in a 1m long baking furnace and then rolled into a roll.
[0067] Preferably, the baking and drying temperature is set to 110±10°C.
[0068] Preferably, the baking and drying time is 1 min to 3 min.
[0069] Example 2 6-DZF-20 battery assembled with grids was subjected to C2 cycle test. All battery packs showed stable trend after 200 cycles. The cycle curves are shown in the attached Fig.10 The impedance of the single cell is about 2.2mΩ, which is relatively low. Fig.12 .
[0070] Embodiment 3:
[0071] Normal lead-calcium rare earth alloy is used to stamp the positive electrode grid 22Y3. After aging hardening, the grid surface is treated.
[0072] First, the 22Y3 grid roll was placed in the prepared sugar-alkali solution and soaked for 48 hours;
[0073] Preferably, the sugar-alkali formula is sodium hydroxide: glucose: pure water = 8:3:100.
[0074] Secondly, put the 22Y3 grid roll into a pure water tank and rinse it repeatedly until the pH value is 7;
[0075] Example 3 The surface of the grid after soaking in sugar alkali is more rough. The SEM of the grid surface (see Figure 2 ).
[0076] Then, the remaining operations are the same as the three steps of Example 2.
[0077] Embodiment 3 The alkali solution soaking time is long and the production efficiency is low. It is not suitable for batch production.
[0078] Embodiment 4:
[0079] Normal lead-calcium rare earth alloy is used to stamp the positive electrode grid 22Y4. After aging hardening, the grid surface is treated.
[0080] First, the 22Y4 grid roll unwinding moves forward at a uniform speed of 1m / min, passes through a 3.5m long sodium carbonate electrolyte heating conductive tank, and immediately passes through three 1m long heated pure water tanks in sequence to clean the alkali solution;
[0081] Preferably, the electrolytic solution is a 2% to 10% sodium carbonate aqueous solution;
[0082] Preferably, the electrolysis is a bidirectional operation, first cathode electrolysis and then anode electrolysis, and the anode is a titanium alloy plate;
[0083] Preferably, the cathode electrolysis current density is 0.5A / dm2 to 1A / dm2, and the time is 3min;
[0084] Preferably, the anode electrolysis current density is 0.5A / dm2 to 1A / dm2, and the time is 30s;
[0085] Preferably, the electrolyte temperature is 50°C to 60°C;
[0086] Preferably, the pure water is heated to 60°C to 80°C.
[0087] Example 4 After bidirectional electrolysis of the cathode and anode, a corrosion layer is formed on the surface of the grid. The SEM image of the grid surface (see Figure 3 ).
[0088] Then, the remaining operations are the same as the three steps of Example 2.
[0089] Example 4 Warm water electrolysis and hot water cleaning increase production energy consumption, and bidirectional electrolysis places higher requirements on production equipment, increases equipment investment, and lengthens the production line.
[0090] Embodiment 5:
[0091] Normal lead-calcium rare earth alloy is used to stamp the positive electrode grid 22Y5. After aging hardening, no pre-treatment is performed and the grid surface is directly electroplated. The operation is carried out according to the second and third steps of Example 2.
[0092] Example 5 Electrodeposition coating surface SEM (see Figure 4 ). The bonding strength between the grid and the coating is weak without pre-treatment, and the coating is prone to cracking or falling off.
[0093] Embodiment 6:
[0094] Normal lead-calcium rare earth alloy is used to stamp the positive electrode grid 22Y2. After aging hardening, the grid surface is treated.
[0095] The first step is the same as the first step of Example 2;
[0096] In the second step, the surface of the pickled grid is subjected to lead-antimony alloy electrodeposition treatment. The specific steps include: the grid passes through a 1m long conductive tank, in which a clarified electrodeposition plating solution is placed, and after 1 minute of electrodeposition, a Pb-Sb alloy coating is formed on the surface of the grid. After that, the grid is sequentially sprayed up and down through four 1m long pure water tanks to be cleaned. After the plating solution is cleaned, the grid is dried by water-absorbing cotton;
[0097] Preferably, the lead antimony electrodeposition formula adopts: 171g / L potassium antimony tartrate, 165g / L tartaric acid, 100mL / L benzenesulfonic acid, and 68.63g / L basic lead carbonate.
[0098] Preferably, the electrodeposition plating tank is left to stand without stirring;
[0099] Preferably, the anode plate is a Pb-Sb alloy lead strip with a thickness of about 2 mm;
[0100] Preferably, the distance between the cathode and the anode is 10 mm to 15 mm;
[0101] Preferably, the electrodeposition current density is 1.0A / dm2 to 2.0A / dm2, and the electrodeposition time is 1min;
[0102] Preferably, the pure water tank is configured for four-stage water washing, and each water inlet is connected to a water storage tank, which is flowing circulating water and can be recycled.
[0103] The third step is the same as the third step of Example 2.
[0104] The main component of the electrodeposited alloy in Example 6 is lead, and the Sb content is not as expected. The SEM and EDS data of the coating (see Figure 5 ).
[0105] After pickling, the stamping oil, dirt and other substances on the surface of the grid are removed, the surface is clean, and it is easy to achieve subsequent electrodeposition. The surface of the grid is roughened. See the attached SEM pictures before and after pickling. Figure 6-7 ; A layer of Pb-Sb alloy is electrodeposited on the surface of the lead-calcium rare earth alloy. The Pb-Sb alloy deposition coating uniformly covers the surface of the grid. SEM images before and after electrodeposition are shown in the attached figure. Figure 8-9 .
[0106] The thickness of the single-sided coating is about 2 μm to 3 μm, and the thickness of the stamped positive electrode grid is about 0.5 mm to 0.8 mm, which is equivalent to a Sb content of about 1.0%.
[0107] The Sb element has a strong binding force with the active material to avoid the formation of a non-conductive barrier layer. The battery test cycle results of the positive grid assembly are shown in the attached Figure 10-11 , 100% DOD cycle 600 times, water loss is about 10g / piece, Sb will not be lost to the negative electrode to cause excessive hydrogen evolution.
[0108] See the attached process flow chart for the grid treatment process Figure 1 This process can not only achieve high-efficiency stamping of the positive electrode grid without the excessive water loss problem of high-antimony alloy grid batteries, but also solve the problem of early capacity loss due to the antimony-free effect.
[0109] The surface treatment process added to the process is simple to implement and the additional cost is very limited, which is mainly due to the increase in water consumption for multi-stage rinsing. Compared with the economic benefits brought by responding to the new national standard of lightweighting, it is negligible. Companies can sell more electric bicycles and achieve lower return rates.
[0110] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made according to the scope of application of the present invention should still fall within the scope of the claims of the present invention.
Claims
1. A manufacturing process for a lightweight positive electrode grid, characterized in that: The following steps are involved: S1. Using lead-calcium rare earth alloy as the positive electrode grid material, a preliminary grid is obtained by stamping; S2. Performing aging hardening treatment on the stamped grid; S3. Surface treatment is performed on the grid after age hardening. The specific steps include: The grid is moved at a constant speed of 1 m / min through a 1 m long methanesulfonic acid tank for immersion; The washed grid is sequentially passed through three 1m long pure water tanks for spray cleaning, and then dried by absorbent cotton. The cleaned grid surface is subjected to lead-antimony alloy electrodeposition treatment, and the specific steps include: passing the grid through a 3m long conductive tank for electrodeposition, and then passing through four 1m long pure water tanks for upper and lower spray cleaning, and then passing through absorbent cotton to absorb water and dry again; S4. The grid after the electrodeposition treatment is passed through a 1m long baking furnace for high temperature drying and then rolled into a roll.
2. The manufacturing process of a lightweight positive electrode grid according to claim 1, characterized in that: The lead antimony electrodeposition formula comprises: 171 g / L potassium antimony tartrate, 165 g / L tartaric acid, 100 mL / L benzenesulfonic acid, and 68.63 g / L basic lead carbonate.
3. The manufacturing process of a lightweight positive electrode grid according to claim 1, characterized in that: The methanesulfonic acid concentration in the methanesulfonic acid tank is 70%, and the pickling time is 1 min to 2 min.
4. The manufacturing process of a lightweight positive electrode grid according to claim 1, characterized in that: During the electrodeposition process, the electrodeposition current density is 0.30A / dm 2 ~2.0A / dm 2 , the electrodeposition time is 1 to 3 minutes.
5. The manufacturing process of a lightweight positive electrode grid according to claim 4, characterized in that: The anode plate is a Pb-Sb alloy lead strip, and the distance between the cathode and the anode is 10mm to 15mm.
6. The manufacturing process of a lightweight positive electrode grid according to claim 1, characterized in that: The baking and drying temperature of the baking oven is set to 110±10° C., and the baking and drying time is 1 min to 3 min.
7. The manufacturing process of a lightweight positive electrode grid according to claim 1, characterized in that: Before the electrodeposition treatment, the grid may be subjected to an additional pretreatment step, such as soaking in a sugar-alkali solution or electrolysis in a sodium carbonate electrolyte, to enhance the roughness of the grid surface and improve the electrodeposition effect.
